Stay positive: self-talk in relation to motivational climate, goal orientation, and self-talk encouragement in tennis - Thibodeaux, J.; Winsler, A. (Research Quarterly for Exercise and Sport, 2022)
Purpose: Motivation among young athletes can be reflected in their self-talk, a behavior that is often encouraged by coaches. Most research on self-talk in sport involves self-report, thus observational studies of the actual self-talk used in sport in relation to athlete motivation and coach support are needed.